An Empirical Basis of Multi-Level Governance Approach: Subnational Mobilisation in the European Union Arena/Çok Boyutlu Yönetisim Yaklasiminin Ampirik Temeli: Avrupa Birligi Arenasinda Ulusalti Hareketlilik - Özçelik, Ali Onur (Eskisehir Osmangazi Üniversitesi sosyal bilimler dergisi, 2014)
The concept of multi-level governance (MLG) and its empirical implications to subnational mobilisation in the EU arena is a key subject of this article. The primary focus here is on the subnational level of analysis and its integration in and interaction with the EU multi-level polity. The obvious reason for writing this article is that the extent to which the interplay between supranational institutions and SNAs has affected intergovernmental relations and caused subnational mobilisation across the EU arena is an empirical matter. Empirically, the creation of MLG in member (and applicant) states and its impact over subnational mobilisation have been exclusively discussed within the context of EU regional policy and related financial incentives. In this respect, this article seeks to explain how the Europeanization of regional policy relates to theoretical concerns with multi-level governance and to find out the extent to which the process of Europeanization contributes to the creation of multi-level modality in member, and particularly, applicant states.